Peningkatan Kesejahteraan Subjektif Remaja Panti Asuhan Melalui Pelatihan Bersyukur - Megawati, Putri, Dr. Sri Lestari, M.Si., Psikolog, Rini Lestari, S.Psi., M.Si., Psikolog (2017)
This study aimed to examine the effect of gratitude training in improving subjective well-being adolescents orphanage. Subject of this research are adolescents orphanage who have subjective well-being of low or medium. This research was a quasi experimental design research, using pretest-postest control group design, which devided subjects into two group that is experimental and control. Two group given pretest,postest and follow up using subjective well being scale. There are two scales to reveal subjective well-being, the scale of flourishing to reveal aspects of life satisfaction and scale SPANE to reveal the affective aspect. The results of this research finds that there are differences in subjective well being of each aspect (life satisfaction and affective) in the experimental group were given training as compared to the control group. It can be concluded that gratitude training shown to be effective in improvement subjective well-being in adolescents orphanage. The results of the qualitative analysis showed that the highest improvement in subjective well-being experienced by adolescents who are willing to initiate communication with caregivers and optimism in achieving goals or expectations. This means that the willingness of adolescents to be open to the caretakers and optimism to support the achievement life satisfaction and positive affective adolescent orphanage